2021
DOI: 10.1094/pdis-11-20-2488-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot Disease Caused by Colletotrichum gloeosporioides on Chaenomeles sinensis in China

Abstract: Chaenomeles sinensis is a shrub or small arbor of the genus Chaenomeles in Rosaceae, which is widely planted in China. It is a kind of garden ornamental plant and has high economic value. Since 2020, a leaf disease occurred on the foliage of C. sinensis at the campus of Nanjing Forestry University, Nanjing, China. After investigating, C. sinensis was found with leaf spot disease at a 100% infection rate, which causing gigantic ornamental loss. Leaf spots are round to irregular distributing on the leaves, in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…exhibit a broad host range, posing threats not only to plants but also to humans, causing subcutaneous infections and keratitis [7,8]. They are also known to infect insects [9] and are responsible for disease in various herbaceous and woody plants, particularly impacting food crops, fruits, vegetables, and ornamental plants, resulting in substantial yield or economic losses [10][11][12][13]. Moreover, reports of multiple Colletotrichum species co-infecting hosts are also increasing [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…exhibit a broad host range, posing threats not only to plants but also to humans, causing subcutaneous infections and keratitis [7,8]. They are also known to infect insects [9] and are responsible for disease in various herbaceous and woody plants, particularly impacting food crops, fruits, vegetables, and ornamental plants, resulting in substantial yield or economic losses [10][11][12][13]. Moreover, reports of multiple Colletotrichum species co-infecting hosts are also increasing [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the steppe zone of Ukraine, in a region with unfavourable climate and industrial pollution, several Chaenomeles species have been successfully introduced and bear fruit, accumulating a high level of the phenolic compounds and showing greater resistance to the common pathogens as compared to other fruit plants (Lykholat et al, 2019). Similarly, Ni et al (2021) concluded low sensitivity of Ch. sinensis foliage to pathogens as only local cases of leaf spot disease caused by Colletotrichum gloeosporioides occurred.…”
Section: Introductionmentioning
confidence: 99%